The efficacy and safety of gabapentin vs. carbamazepine in patients with primary trigeminal neuralgia: A systematic review and meta-analysis - Zhao, Xin; Ge, Shuyu (Frontiers in Neurology, 2023)
Background Drug therapy is the most commonly used treatment for primary trigeminal neuralgia (PTN), in which carbamazepine is the first-line drug. Recently, the anti-epileptic drug gabapentin has also been widely used in patients with PTN, but whether it can be used as a substitute for carbamazepine still needs to be verified. Our study aimed to assess the safety and efficacy of gabapentin vs. carbamazepine as a treatment for PTN. Methods We searched seven electronic databases for studies published as of 31 July 2022. All randomized controlled trials (RCTs) of gabapentin vs. carbamazepine on patients with PTN that met the inclusion criteria were included. Meta-analysis was conducted using Revman 5.4 and Stata 14.0, in which forest plots, funnel plots, and sensitivity analysis were performed. Mean difference (MD) and odds ratio (OR) with 95% confidence intervals (CIs) were used for the measurement indicators of continuous and categorical variables, respectively. Results A total of 18 RCTs with 1,604 patients were eventually identified. The meta-analysis showed that compared with the carbamazepine group, the gabapentin group significantly improved the effective rate (OR = 2.02, 95% CI 1.56 to 2.62, P < 0.001), reduced the adverse event rate (OR = 0.28, 95% CI 0.21 to 0.37, P < 0.001), and improved the visual analog scale (VAS) score (MD = −0.46, 95% CI −0.86 to −0.06, P = 0.03). Although the funnel plot showed evidence of publication bias, the sensitivity analysis revealed the stability of the results. Conclusion The current evidence showed that gabapentin may be superior to carbamazepine in relation to efficacy and safety in patients with PTN. It is crucial that more RCTs are conducted to confirm the conclusion in the future.